Nonequilibrium plasmon emission drives ultrafast carrier relaxation dynamics in photoexcited graphene - Hamm,JM; Page,AF; Bravo-Abad,J; Garcia-Vidal,FJ; Hess,O (Physical Review B, 2016)
The fast decay of carrier inversion in photoexcited graphene has been attributed to optical phonon emission and Auger recombination. Plasmon emission provides another pathway that, as we show here, drives the carrier relaxation dynamics on ultrafast timescales. In studying the nonequilibrium relaxation dynamics we find that plasmon emission effectively converts inversion into hot carriers, whose energy is then extracted by optical phonon emission. This mechanism not only explains the observed fs-lifetime of inversion but also offers the prospect for atomically thin ultrafast plasmon emitters.